Enhancing HIV-1 Nef Penetration into Mammalian Cells as an Antigen Candidate - Saba Davoodi; Azam Bolhassani; Seyed Mehdi Sadat; Shiva Irani (Pasteur Institute of Iran, 2019)
Introduction: The human immunodeficiency virus type 1 (HIV-1) Nef regulatory protein is known as a candidate for the design of therapeutic HIV DNA and protein vaccines. One of the limitations of these vaccines is the inability of DNA and protein to pass through the cell membrane. Various delivery systems have been developed to transfer DNA and protein into cells. Cell penetrating systems such as MPG and Cylop-1 are among delivery systems, which can deliver DNA and protein cargoes into the cells, respectively. Methods: In this study, we produced the recombinant Nef protein in Escherichia coli expression system. Then, the formation of CPP/DNA and CPP/protein nanoparticles was confirmed by agarose gel retardation, scanning electron microscope (SEM), Zetasizer and SDS-PAGE, and their stability was evaluated against nucleases and proteases. Finally, the delivery of the nanoparticles into HEK-293T cells was assessed by fluorescent microscopy, flow cytometry, and western blotting. Results: Our data confirmed the formation of stable nanoparticles through non-covalent bonds with a diameter of less than 200 nm. Moreover, the results of fluorescence microscopy, flow cytometry, and western blotting demonstrated that these CPPs could successfully deliver the Nef protein and DNA into HEK-293T cells. Conclusion: Our results indicated that the MPG and CyLoP-1 CPPs are suitable candidates for the delivery of DNA and protein cargoes into mammalian cells, respectively.